Lasers: Low‐Threshold Whispering Gallery Mode Lasing from Self‐Assembled Microspheres of Single‐Sort Conjugated Polymers (Advanced Optical Materials 10/2017). Issue 10 (16th May 2017) - Kushida, Soh; Okada, Daichi; Sasaki, Fumio; Lin, Zhan‐Hong; Huang, Jer‐Shing; Yamamoto, Yohei
Abstract : Whispering gallery mode lasing upon femtosecond laser pumping is demonstrated with self‐assembled, single‐component conjugated polymer microspheres in article number1600123 by Yohei Yamamoto and co‐workers. The lasing threshold of the presented laser is as low as one μJ per square centimeter. The threshold fluence is further reduced by mounting the microspheres on an Ag‐coated substrate, achieving values amongst the lowest ever reported with dye‐doped polymer lasers.